Erastin inhibits porcine epidemic diarrhea virus replication in Vero cells - Zhang, Hongliang; Li, Yingguang; Yang, Ruimei; Xiao, Ling; Dong, Shaoming; Lin, Jiaxu; Liu, Gang; Shan, Hu (Frontiers in Cellular and Infection Microbiology, 2023)
Background Porcine epidemic diarrhea virus (PEDV), an intestinal pathogenic coronavirus, has caused significant economic losses to the swine industry worldwide. At present, there are several treatment methods, but there is still a lack of clinically effective targeted drugs, new antiviral mechanisms and drugs need to be explored. Methods In this study, we established a model of erastin versus ferrostatin-1 treatment of Vero cells, and then detected virus proliferation and gene expression by RT-qPCR through PEDV infection experiments. Results We demonstrated for the first time that erastin significantly inhibited the replication of PEDV upon entry into cells; Vero treated with erastin significantly regulated the expression of three genes, NRF2, ACSL4 and GPX4, notably erastin regulated the expression of these three genes negatively correlated with the expression induced by PEDV virus infection. Conclusions Since NRF2, ACSL4 and GPX4 are classical Ferroptosis genes, this study speculates that erastin may inhibit the replication of PEDV in Vero cells in part through the regulation of ferroptosis pathway, and erastin may be a potential drug for the treatment of PEDV infection.